POTENSI SEKTOR EKONOMI DAN KETERKAITANNYA DENGAN KESEMPATAN KERJA DI KABUPATEN OGAN KOMERING ULU PROVINSI SUMATERA SELATAN - Yuliana, Yuliana (Publikasi Penelitian Terapan dan Kebijakan, 2012)
In the development of a region is necessary to superior economic sectors to be reliable for the development of the area. The purpose of research is to 1) Determine the economic sectors that have potential to be developed in order to increase economic activity in Ogan Komering Ulu, 2) Knowing employment in economic sectors that have potential in Ogan Komering Ulu. Data were analyzed by method 1) Location Quotient, 2) Employment elasticity. Based on the results of this study concluded that 1) the value of LQ in Ogan Komering Ulu year 1993-2002 there are 3 (three) sectors that have the potential to be developed, the Agricultural Sector with the highest potential value of LQ (1.45) and then followed the Building Sector (1.17) and The Services Sector (1.14). The third sector is a sector basis for Ogan Komering Ulu. 2) The economic sectors that could potentially positive effect on employment in Ogan Komering Ulu. Advice can be given as follows : The first, the Government is expected to Ogan Komering Ulu proactively to improve the quality of human resources, through training / training or sending employees to continue their studies to a higher level. The second, for always encouraging private investment and increase its investment toperform Ogan Komering Ulu area.